Evaluation of bone mineral density and its correlation with homocysteine and other biochemical bone markers in postmenopausal women - P., Gopinath; Ravoof, Abdul (International Journal of Research in Orthopaedics, 2018)
Background: Osteoporosis is more common in post-menopausal women. Early detection of bone loss by bone mineral density helps to confirm the diagnosis of osteoporosis and assesses the future risk of osteoporotic fractures. Recent studies have revealed the association between increased plasma concentrations of homocysteine (Hcy), and reduced bone mineral density. Nevertheless, inconsistencies persist in the literature. Thus, the need for this study arose to investigate the possible relationship between serum Hcy status and bone mineral density on a group of post-menopausal women. The objective of the study was to assess bone mineral density (BMD) in postmenopausal women and to correlate the same with biochemical bone markers like homocysteine, serum alkaline phosphatase (ALP), calcium and phosphorous levels. Methods: One hundred (100) postmenopausal women were recruited to enter this cross-sectional study. Out of which 86 postmenopausal females, were grouped into osteopenic and osteoporotic based on low t –scores. Bone mineral density (BMD) was measured by dual-energy x-ray absorptiometry (DEXA) and serum Hcy, serum ALP, calcium and phosphorus levels were estimated. The relationship of Hcy with BMDand other biochemical markers was estimated using Pearson’s correlation. Results: Serum Hcy levels were significantly higher in osteoporotic women when compared to other BMD groups, and were inversely correlated with BMD. No statistical difference was seen with other biochemical bone markers like calcium, Phosphorus and ALP. Conclusions: This study shows that Hcy status is associated with BMD in osteoporotic postmenopausal women. BMD evaluation in postmenopausal women with high Hcy levels may have prognostic and therapeutic potentials, which needs to be explored through further Prospective studies.